Prevalence of Carbapenem-Resistant Hypervirulent Klebsiella pneumoniae and Hypervirulent Carbapenem-Resistant Klebsiella pneumoniae in China Determined via Mouse Lethality Tests - Hu, Dakang; Chen, Wenjie; Zhang, Qi; Li, Meng; Yang, Zehua; Wang, Yong; Huang, Yunkun; Li, Gang; Tian, Dongxing; Fu, Pan; Wang, Weiwen; Ren, Ping; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To investigate the epidemiology of carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-HvKP) and hypervirulent carbapenem-resistant Klebsiella pneumoniae (Hv-CRKP). Methods Totally 436 K. pneumoniae strains were collected from 7 hospitals in mainland China between 2017.01 and 2018.02. Sequence types, serotypes, antimicrobial-resistance and virulence genes were analyzed. Additionally, string test, capsule stain, Periodic Acid Schiff stain, fitness analysis, quantitative real-time PCR and mouse lethality test were also performed. Molecular combinations were used to screen putative blaKPC(+)-HvKP and Hv-blaKPC(+)-KP, followed by the confirmation of mouse lethality test. Results Diverse detection rates were found for the virulence genes, ranging from c-rmpA (0.0%) to entB (100.0%). According to the molecular criteria, 127, 186, 9 and 26 strains were putatively denoted as HvKP, blaKPC(+)-KP, blaKPC(+)-HvKP and Hv-blaKPC(+)-KP. Mouse lethality test confirmed 2 blaKPC(+)-HvKP strains (JS184 and TZ20) and no Hv-blaKPC(+)-KP. JS184 showed K2 serotype, thin capsule, positive exopolysaccharid and string test. TZ20 presented K20 serotype, thin capsule, negative exopolysaccharide and string test. Compared with the positive control NTUH-K2044, equal galF expression and growth curves were confirmed for JS184 and TZ20. Conclusions Molecular determination of CR-HvKP and Hv-CRKP brings remarkable bias compared with mouse lethality test. The exact prevalence of CR-HvKP is less than 1.0%, which of Hv-CRKP is much lower.